Household Consumption Analysis of Gambir Farmers in Harau District, Limapuluh Kota Regency - Ratna Agustia; Nin Patri Enanti; Yuliatri Yuliatri; Sulastri Sulastri; Fefriyanti DS (Journal of Agriculture, 2026)
Gambir (Uncaria gambir Roxb.) is a strategic plantation commodity in Indonesia, with West Sumatra Province contributing 80–90% of national exports. Limapuluh Kota Regency, particularly Harau District, is one of the main production centers. Despite its economic potential, gambir farmers face significant challenges, including price volatility, limited bargaining power, and low product quality due to traditional processing methods. These conditions directly affect farm household income stability and, consequently, household consumption patterns. This study aims to analyze total household consumption and its composition — both food and non-food expenditures—among gambir-farming households in Harau District, Limapuluh Kota Regency. The research employed a survey method with a quantitative descriptive approach. The sample consisted of 30 purposively selected gambir farmers from Nagari Harau, Harau District. Data were collected through structured and unstructured interviews, direct observation, and literature studies. The results revealed that the average total household consumption reached IDR 3,716,883 per month (IDR 44,602,600 per year). Food consumption accounted for IDR 2,283,583 per month (61.4% of total consumption), with animal-based protein (IDR 756,667/month) being the highest expenditure component, substantially exceeding staple food expenditure (IDR 454,333/month). Non-food consumption amounted to IDR 1,433,300 per month (38.6%), dominated by transportation (IDR 525,000/month) and education (IDR 529,000/month). Notably, only 20% of respondents paid health insurance independently, while 50% had no regular health expenditure, indicating uneven access to healthcare services.